(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
In the rapidly changing media landscape, journalism students require not only linguistic competence but also the ability to apply English in authentic professional contexts. This paper explores innovative strategies for teaching professionally-oriented English to journalism students by integrating interdisciplinary approaches and modern teaching methods. The study highlights how combining journalism-specific content with English language instruction enhances students’ critical thinking, media literacy, and communication skills. Special attention is given to project-based learning, case studies, collaborative tasks, and digital tools that foster authentic journalistic practices such as news reporting, interviewing, and editorial writing. The findings emphasize that interdisciplinary teaching not only improves students’ language proficiency but also equips them with the practical skills necessary for success in their future careers in media and communication.